The basic components for the theory of Ulul Albab teachers' professional development programme - Subirim @ Subirin, Nor Adzimah; Alwi, Nor Hayati; Mohd Fakhruddin, Fathiyah; Abdul Manaf, Umi Kalthom; Salim, Siti Suria; Hassan, Siti Aishah; Othman, Shamsudin; Mohd Ali, Nurul Jawahir (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Ulul Albab generation is the main target outcome of Ulul Albab program. Objectives, mission and vision have been drawn up beautifully to achieve the aim of having a generation who is able to use their mind and heart to understand the essence of life based on strong foundation of Al-Quran epistemology. It is therefore, the students of Ulul Albab program that need to be educated, guided, facilitated, and monitored properly in order to appropriately become an Ulul Albab generation. Therefore, teachers are expected to play their role as a group who will be responsible to assist the students in the system. Because of that, teachers of the Ulul Albab program will be the main focus of this research as the key implementer of Ulul Albab curriculum. The purpose of this research is to examine the elements of professional development (PD) for teachers of Ulul Albab program. The teachers here are referring to all teachers regardless of field of expertise, religious or academic. Six experts from various fields have been interviewed in order to investigate the relevancy of developing teachers’ professional development for Ulul Albab teachers. Open coding grounded theory approach has been used to analyse the data, whereby, the theory develops from the data as it is collected and analysed inductively. The findings have shown that there are three basic components, namely, the Input, the Process/Mechanism and the Outcome in which several elements have been drawn up from the findings such as the selection of the right teachers, teacher’s traits, teachers’ training (pre-service and in-service), learning environment, and the nature of teachers’ professional development for the Ulul Albab program. The experts collaboratively agree that teachers’ professional development will benefit more to the Ulul Albab program. In a nutshell, it is crucial to prepare the teachers with a systematic and dynamic professional development according to the concept of Ulul Albab, for the sake of moulding future generation that would be the frontliner of Muslim civilization in the country.